(untitled) (Research, Society and Development, 2022)
Through a review of the bibliographic base was identified the potential and difficulties of using biofuels based on babassu culture for use as aviation biofuel. Babassu palm is one of the most important crops for family farming in the north and northeast of Brazil due to its vast use potential. From babassu oil, by transesterification, good quality biodiesel can be obtained. However, it does not have the properties necessary to be used as aviation biofuel. Researches with biofuels from this culture and cultures with a similar organic profile were analyzed pointing out the feasibility of these biofuels as a mixture in aviation kerosene, nevertheless, these biofuels present several problems when used alone. Among the physical-chemical properties analyzed, the freezing point was a critical factor for not using these biofuels. This review points out the best results to improve the physicochemical properties of babassu biofuels to use as aviation fuel and present an important social factor to this palm uses.